The association between the Glutathione S-transferase polymorphisms and addiction to opioids and methamphetamine in the Iranian population - Eskandarion, Mohammad Reza; Jafaripour, Simin; Heidari, Farid; Talebi, Elham; Taleghani, Maryam Rezakhani; Maserat, Neda; Forutan, Maryam; Ghorbani, Raheb; Gharehdaghi, Jaber; Shirkoohi, Reza; Raoofian, Reza (Frontiers in Psychiatry, 2024)
IntroductionGlutathione S-transferase (GST) has the ability to detoxify the cellular environment of xenobiotic compounds and by-products of oxidative stress. The expression levels of GST genes and their polymorphisms are associated with various human diseases. Methamphetamine and opiate addiction also account for a significant proportion of SUDs in Iran. Considering the oxidative stress induced by morphine and methamphetamine and the potential of GST as a therapeutic option for SUD, we aimed to investigate the association of common genetic variations of two genes from GST family, GSTT1 and GSTM1, with addiction to morphine and METH in Iranian population.Material and methodsA total of 160 blood and urine samples were randomly collected from 50 opiums and 30 methamphetamine users and 80 healthy controls. All samples were processed by thin layer chromatography (TLC), high performance liquid chromatography, and Gas Chromatography-Mass Spectrometry (GC-MS) techniques to detect opium alkaloids (morphine, codeine, papaverine, noscapine, etc.), methamphetamine stimulants, and other legal and illegal drugs. The genotypes of GSTM1 and GSTT1 polymorphisms were determined by PCR. Statistical analysis was performed using the SPSS. This project was approved by the Research Ethics Committee of Legal Medicine Organization, Tehran, Iran.ResultsA statistically significant association was observed between the GSTM1 polymorphisms and morphine addiction under a recessive genetic model. The reference group consisted of pooled n/p and p/p genotypes, with an odds ratio (OR) of 2.15, a 95% confidence interval (CI) of 1.05 to 4.39, and a P-value of 0.03. In contrast, there was no statistically significant association between genetic variations in the GSTT1 gene and morphine or methamphetamine addiction. The results revealed no significant association between GSTT1 and GSTM1 allele frequencies and morphine and methamphetamine addiction when divided into risk allele carriers and noncarriers.ConclusionThese findings suggest that the GSTM1 gene may be involved in the development of morphine addiction. However, further studies with larger sample sizes are required to verify these results and investigate the underlying molecular mechanisms.